Divine images and human imaginations in Ancient Greece and Rome: [conference "Images of gods - images for gods" at the University of Erfurt in June 2007] - Mylonopulos, Giannēs (Religions in the Graeco-Roman world, 2010)
Introduction : divine images versus cult images : an endless story about theories, methods, and terminologies / Joannis Mylonopoulos -- A pantheon without attributes? : goddesses and gods in Minoan and Mycenean iconography / Fritz Blakolmer -- Aniconism and the notion of "primitive" in Greek antiquity / Milette Gaifman -- Finding the gods : Greek and Cypriot votive korai revisited / Catherine M. Keesling -- Gods and statues : an approach to archaistic images in the fifth century BCE / Fernande Hölscher -- Greek priests and "cult statues" : in how far are they unnecessary? / Vinciane Pirenne-Delforge -- Theseus and the stone : the iconographic and ritual contexts of a Greek votive relief in the Louvre / Gunnel Ekroth -- Odysseus with a trident : the use of attributes in ancient Greek imagery / Joannis Mylonopoulos -- The life story of a cult statue as an allegory : Kallimachos' Hermes perpheraios / Ivana Petrovic -- Arcadian cult images between religion and politics / Tanja Scheer -- Synnaos theos : images of Roman emperors in Greek temples / Dirk Steuernagel -- Simulacra deorum versus ornamenta aedium : the status of divine images in the temples of Rome / Sylvia Estienne -- The dedication of cult statues at the altar : a Roman pictorial formula for the introduction of new cults / Katja Moede -- Ornamenta, monumenta, exempla : Greek images of gods in the public spaces of Constantinople / Alessandra Bravi